RELATIONSHIP BETWEEN TOTAL LENGTH AND GILL SURFACE AREA IN ORANGE SPOTTED GROUPER, EPINEPHELUS COIOIDES (Hamilton, 1822) - Mohammed, F. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
The present study deals with the estimation of gill surface area for orange spotted grouper (Epinephelus coioides) collected from Iraqi marine water, north west Arabian Gulf. In the laboratory, fishes were separated in to five different length groups ranging from 200-325 mm and weight range of 108.8-582.2g. Absolute and relative total gill surface area (GSA) were estimated for 33 fish from different lengths. Statistical analysis of results revealed that there were significant differences (P0.05) between secondary lamellae (Bl) in different length groups. Statistical analysis showed also that there were significant differences (P